Active energy ray-curable varnish composition

JP2025020863APending Publication Date: 2025-02-13SAKATA INX
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023124486
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-13

AI Technical Summary

Benefits of technology

【0013】 本発明の活性エネルギー線硬化性ワニス組成物は、ラミコート加工による印刷物の作成における印刷適性が高く、かつ、ラミコート加工により得られる印刷物の印刷物品質を高めることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025020863000001_ABST
    Figure 2025020863000001_ABST
Patent Text Reader

Abstract

To impart "printing suitability" and "printed material quality" to a varnish composition used for the preparation of printed materials by Lamicoat processing.SOLUTION: The present invention provides an active energy ray-curable varnish composition for a laminate obtained by overlaying a polyolefin film onto a coating layer composed of the active energy ray-curable varnish composition formed on a substrate, curing the coating layer through active energy ray irradiation to form a cured layer, and then peeling the polyolefin film from the cured layer. The active energy ray-curable varnish composition comprises: (1) 10.0-40.0 mass% of a styrene-based resin (A) relative to the total composition, with the mass ratio of styrene being 95% or more, and the acid value being either 0 mgKOH / g or 0-10 mgKOH / g; (2) a polymerizable monomer (B) comprising a difunctional polymerizable compound (B1) with a polyol ethylene oxide adduct skeleton; (3) an initiator (C); and (4) 0.1-0.5 mass% of a silicone-based compound (D) relative to the total composition.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a varnish composition that can be cured with active energy rays (active energy ray-curable varnish composition), and more specifically to an active energy ray-curable varnish composition used in producing printed matter by lamicoat processing. [Background technology]

[0002] As one method for producing a printed matter, a technique called "Lami-coat (LC) processing" is known (Patent Document 1, etc.). In producing a printed matter by the Lami-coat processing, first, an active energy ray curable varnish composition is coated on the surface of a substrate, which is a printed matter (Step A). ​​Next, while a polyolefin film is pressed against the coating film of the active energy ray curable varnish composition (coating film in a wet state before curing) coated on the surface of the substrate (Step B), the coating film of the active energy ray curable varnish composition is irradiated with active energy rays through the polyolefin film, thereby forming the coating film into a cured layer (Step C). After that, the polyolefin film is peeled off from the cured layer of the active energy ray curable varnish composition (Step D).

[0003] Several active energy ray curable varnish compositions have been proposed for use in the production of printed matter by lamicoating (see Patent Documents 2 to 6). Patent Document 2 discloses an active energy ray curable varnish composition containing a chlorinated polypropylene resin with a specified chlorine content, and is said to provide a cured product layer with excellent adhesion to a substrate, glossiness, cosmetic properties, and yellowing resistance. Patent Document 3 discloses an active energy ray curable varnish composition containing a phosphoric acid compound, and is said to provide a cured product layer with excellent adhesion to a substrate, glossiness, cosmetic properties, and yellowing resistance. Patent Document 4 discloses an active energy ray curable varnish composition containing a specified styrene-acrylic resin, and is said to provide a cured product layer with excellent adhesion to a substrate, glossiness of a coating film, cosmetic properties, and yellowing resistance. Patent Document 5 discloses an active energy ray curable varnish containing a polar functional group-containing (meth)acrylic resin and an alkyl group-containing (meth)acrylic resin, and is said to provide a cured product layer that can suppress deterioration of glossiness over time. Patent Document 6 discloses an active energy ray-curable varnish containing a specific styrene-acrylic resin and a photopolymerizable monomer, and the varnish is said to have fluidity for achieving good cosmetic properties. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2007-90162 A [Patent Document 2] Patent Publication No. 2021-80354 [Patent Document 3] JP 2021-147494 A [Patent Document 4] Patent No. 5978497 [Patent Document 5] Patent No. 5617610 [Patent Document 6] JP 2012-136618 A Summary of the Invention [Problem to be solved by the invention]

[0005] Prints created by lamicoat processing are characterized by high surface leveling of the resulting cured layer, as the varnish applied to the substrate is cured while being pressed with a film; furthermore, since it is less susceptible to curing inhibition by oxygen, it is said that it is possible to reduce the amount of curing energy and photopolymerization initiator required.

[0006] In addition, varnish compositions used to create printed materials by lamicoat processing are required to have high "printing suitability", such as being easily cured by active energy rays (curability) and being easy to peel off from the cured coating film (cured layer) (peelability); and further, high "print quality" is required, such as high adhesion of the cured layer of the varnish formed on the substrate, high surface hardness of the cured layer (scratch resistance, etc.), high gloss, high surface slipperiness of the cured layer, no blocking even when the cured layers come into contact with each other, and, depending on the application of the printed material, flexibility and stretchability of the cured layer (suppression of cracking of creases).

[0007] The present invention aims to impart the above-mentioned "printability" and "print quality" to a varnish composition used in producing printed matter by lamicoating. For example, when an attempt is made to increase the flexibility or stretchability of a cured layer of a varnish composition, the peelability of a film from the cured layer tends to decrease. Therefore, the present invention aims to maintain a good balance between "printability" and "print quality" by adjusting the composition of the varnish composition. [Means for solving the problem]

[0008] That is, the present invention relates to an active energy ray-curable varnish composition used for producing printed matter by lamicoating, as shown below. [1] An active energy ray-curable varnish composition for a laminate obtained by overlaying a polyolefin film on a coating layer made of an active energy ray-curable varnish composition formed on a substrate, curing the coating layer by irradiation with active energy rays to form a cured layer, and peeling the polyolefin film from the cured layer, An active energy ray-curable varnish composition comprising the following (1) to (4): (1) 10.0 to 40.0 mass% of a styrene-based resin (A) relative to the entire composition, the styrene mass ratio being 95% or more and the acid value being 0 mgKOH / g or 0 to 10 mgKOH / g; (2) a polymerizable monomer (B) including a bifunctional polymerizable compound (B1) having an ethylene oxide adduct skeleton of a polyol; (3) 0.1 to 20.0 mass% of an initiator (C) relative to the entire composition; and (4) 0.1 to 0.5 mass% of a silicone-based compound (D) relative to the entire composition.

[0009] The present invention preferably relates to the following active energy ray-curable varnish composition. [2] The active energy ray-curable varnish composition according to [1] above, wherein the styrene-based resin (A) is a styrene homopolymer. [3] The active energy ray-curable varnish composition according to [1] or [2] above, wherein the styrene-based resin (A) has a mass average molecular weight of 3,000 to 8,000.

[0010] [4] The active energy ray-curable varnish composition according to any one of the above [1] to [3], wherein the polyol of the bifunctional polymerizable compound (B1) having an ethylene oxide adduct skeleton of the polyol is a polyol having 4 to 8 carbon atoms. [5] The active energy ray-curable varnish composition according to any one of the above [1] to [4], wherein the bifunctional polymerizable compound (B1) having an ethylene oxide adduct skeleton of a polyol has an ethylene oxide addition number of 3 to 8. [6] The active energy ray-curable varnish composition according to any one of the above [1] to [5], wherein the bifunctional polymerizable compound (B1) having an ethylene oxide adduct skeleton of a polyol is a diacrylate of a 5-mol ethylene oxide adduct of 1,6-hexanediol (5EO-HDDA). [7] The active energy ray-curable varnish composition according to any one of [1] to [6] above, wherein the content of the bifunctional polymerizable compound (B1) having an ethylene oxide adduct skeleton of the polyol is 20.0 mass% or less based on the total composition.

[0011] [8] The active energy ray-curable varnish composition according to any one of the above [1] to [7], wherein the initiator (C) has a hydroxyalkylphenone structure. [9] The active energy ray-curable varnish composition according to any one of [1] to [8] above, wherein the content of the initiator (C) is 8.0 mass % or more based on the total mass of the composition.

[0012]

[10] The active energy ray-curable varnish composition according to any one of the above [1] to [9], wherein the polymerizable monomer (B) further contains a tri- or higher functional polymerizable compound (B2) having an ethylene oxide adduct skeleton of a polyol.

[11] The active energy ray-curable varnish composition according to

[10] above, wherein the polyol of the tri- or higher functional polymerizable compound (B2) having an ethylene oxide adduct skeleton of a polyol is trimethylolpropane.

[12] The active energy ray-curable varnish composition according to

[10] or

[11] above, wherein the tri- or higher functional polymerizable compound (B2) having an ethylene oxide adduct skeleton of a polyol has an ethylene oxide addition number of 1 to 12.

[13] The active energy ray-curable varnish composition according to any one of

[10] to

[12] above, wherein the content of the tri- or higher functional polymerizable compound (B2) having an ethylene oxide adduct skeleton of the polyol is 10.0 to 30.0 mass% based on the total mass of the composition. Effect of the Invention

[0013] The active energy ray-curable varnish composition of the present invention has high printability in the production of printed matter by lami-coating, and can improve the print quality of printed matter obtained by lami-coating. [Brief description of the drawings]

[0014] [Figure 1] FIG. 2 is a diagram showing a method for producing a printed matter in the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] 1. Composition of active energy ray-curable varnish composition The active energy ray-curable varnish composition of the present invention (hereinafter also simply referred to as the "varnish composition") contains at least 1) a styrene-based resin (A), 2) a polymerizable monomer (B), 3) an initiator (C), and 4) a silicone-based compound (D), and may further contain 5) other optional components.

[0016] 1-1. Styrene-based resin (A) The styrene resin (A) contained in the varnish composition is a resin containing styrene as a monomer unit. The styrene constituting the monomer unit of the styrene resin (A) may be styrene or other styrenes such as α-methylstyrene and vinylstyrene, and is preferably styrene.

[0017] The mass content of styrene in the styrene resin (A) is 95% or more, preferably 98% or more, and may be 100% (i.e., styrene homopolymer). When the mass content of styrene in the styrene resin (A) is 95% or more, the adhesion of the cured layer in the printed matter obtained by lami-coating is likely to be increased, the film peelability is also improved, and the cured layer is likely to have high surface hardness (high scratch resistance); and the gloss of the printed matter is likely to be increased.

[0018] The acid value of the styrene resin (A) is 0 mgKOH / g or 0 to 10 mgKOH / g, preferably 0 mgKOH / g or 0 to 5 mgKOH / g, more preferably 0 mgKOH / g. In other words, if the styrene resin (A) is a styrene homopolymer, its acid value can be 0 mgKOH / g. The lower the acid value of the styrene resin (A), the higher the adhesion between the cured layer of the varnish composition and the substrate in the printed matter obtained by lamination coating, and the higher the scratch resistance of the cured layer.

[0019] The mass average molecular weight of the styrene-based resin (A) is not particularly limited, but may be 3000 to 8000. In order to increase the surface hardness of the cured layer of the varnish composition, it is preferable that the molecular weight of the styrene-based resin (A) is high; on the other hand, in order to reduce the viscosity of the varnish composition, it is preferable that the molecular weight of the styrene-based resin (A) is low.

[0020] The styrene-based resin (A) may or may not have other structural units other than styrene as monomer structural units. Examples of other structural units include (meth)acrylic acid ester monomers. Examples of (meth)acrylic acid esters include alkyl (meth)acrylates having linear or branched alkyl chains such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, pentyl, hexyl, 2-heptyl, 2-ethylhexyl, 2-ethylbutyl, nonyl, dodecyl, lauryl, and stearyl; (meth)acrylates having amino groups such as 2-(N,N-dimethylamino)ethyl (meth)acrylate and 3-(N,N-dimethylamino)propyl (meth)acrylate; (meth)acrylates having hydroxyl groups such as 2-hydroxyethyl (meth)acrylate and hydroxypropyl (meth)acrylate; and (meth)acrylates having epoxy groups and (meth)acrylates having amide groups.

[0021] The content (solid content) of the styrene-based resin (A) in the varnish composition is 10.0% by mass or more, preferably 15.0% by mass or more, based on the entire varnish composition; on the other hand, it is 40.0% by mass or less, preferably 30.0% by mass or less. In order to improve the film peelability and scratch resistance of the cured layer of the printed matter, it is preferable to increase the content of the styrene-based resin (A). On the other hand, in order to improve the printing characteristics of the varnish composition or to increase the flexibility and stretchability of the cured layer to suppress cracking of the printed matter, it is preferable to keep the content of the styrene-based resin (A) below a certain level.

[0022] 1-2. Polymerizable monomer (B) The polymerizable monomer (B) contained in the varnish composition may be a monomer or oligomer having at least one polymerizable reactive group, such as a (meth)acryloyl group, in the molecule. The polymerizable monomer (B) contains at least a bifunctional polymerizable compound (B1) having an ethylene oxide adduct skeleton of a polyol; it preferably further contains a trifunctional or higher functional polymerizable compound (B2) having an ethylene oxide adduct skeleton of a polyol; and may contain another polymerizable compound (B3).

[0023] 1-2-1. Bifunctional polymerizable compound having an ethylene oxide adduct skeleton of polyol (B1) At least a part of the polymerizable monomer (B) is a bifunctional polymerizable compound (B1) having an ethylene oxide adduct skeleton of a polyol. The "ethylene oxide adduct skeleton of a polyol" refers to a compound in which ethylene oxide (C) is bonded to a hydroxyl group of a polyol (polyhydric alcohol). 2 H 4O) is added to the polyol. The polyol of the bifunctional polymerizable compound (B1) may be either an aromatic or an aliphatic polyol, but an aliphatic polyol is sometimes preferred. The polyol of the bifunctional polymerizable compound (B1) preferably has 4 to 8 carbon atoms. Specific examples of the polyol include aliphatic diols such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,2-pentanediol, 1,3-pentanediol, 1,2-hexanediol, 1,6-hexanediol, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 3-methyl-1,3-butanediol, 2-ethyl-2-methyl-1,3-propanediol, 2-ethyl-1,3-hexanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol, tetrapropylene glycol, and polyethylene glycol; and aromatic diols such as bisphenol A and bisphenol F.

[0024] The number of ethylene oxides added to the polyol of the bifunctional polymerizable compound (B1) may be 1 or more, preferably 3 or more; preferably 8 or less. The more ethylene oxides added to the polyol of the bifunctional polymerizable compound (B1), the more likely it is that the cured layer of the varnish composition will have improved flexibility and stretchability, and the more likely it is that cracks in the lines of the printed matter will be suppressed. On the other hand, if the number of ethylene oxides added to the polyol of the bifunctional polymerizable compound (B1) is too large, the scratch resistance of the cured layer in the printed matter will tend to decrease, or the film peelability from the cured layer will tend to decrease.

[0025] The bifunctional polymerizable compound (B1) may be a compound obtained by reacting an ethylene oxide adduct of a polyol with a compound having a polymerizable functional group (e.g., a (meth)acryloyl group); a compound obtained by esterifying an ethylene oxide adduct of a polyol with two (meth)acrylic acids is preferable. The (meth)acrylic acid is one or both of acrylic acid and (meth)acrylic acid. The bifunctional polymerizable compound (B1) is preferably a diacrylate (5EO-HDDA) of an ethylene oxide adduct of 5 moles of 1,6-hexanediol.

[0026] The content of the polymerizable compound (B1) in the varnish composition is preferably 20% by mass or less, more preferably 15% by mass or less, based on the total composition; on the other hand, it is preferably 3% by mass or more, more preferably 4% by mass or more. The content of the polymerizable compound (B1) in the varnish composition is preferably 65% ​​by mass or less, more preferably 55% by mass or less, based on the total of the polymerizable monomers (B); on the other hand, it is preferably 5% by mass or more, more preferably 10% by mass or more. When the polymerizable compound (B1) is at a certain level or more, the flexibility and stretchability of the cured layer of the varnish composition are likely to increase, and cracking of the printed matter is likely to be suppressed. On the other hand, when the content of the polymerizable compound (B1) is too high, the film peelability of the cured layer in the printed matter is likely to decrease, and the scratch resistance of the cured layer is also likely to decrease.

[0027] 1-2-2. Trifunctional or higher polymerizable compound having an ethylene oxide adduct skeleton of polyol (B2) The polymerizable monomer (B) may contain a trifunctional or higher polymerizable compound (B2) having an ethylene oxide adduct skeleton of a polyol. The trifunctional or higher polymerizable compound (B2) is preferably a polyol having three or more alcoholic hydroxyl groups. Specific examples of the trifunctional or higher polymerizable compound (B2) include glycerin, propane-1,1,3-triol, 1,2,3-butanetriol, 1,2,4-butanetriol, 1,1,4-butanetriol, 2-(hydroxymethyl)-1,3-propanediol, 2-methylpropane-1,1,1-triol, 2-methyl-1,2,3-propanetriol, trimethylolethane, 2,3,4-pentanetriol, and 1,2,3-pentanetriol. , 1,2,4-pentanetriol, 1,2,5-pentanetriol, 1,3,4-pentanetriol, 1,3,5-pentanetriol, 2-methyl-1,2,4-butanetriol, 3-methyl-1,2,3-butanetriol, 2-methylbutane-1,2,3-triol, 2-ethylbutane-1,2,3-triol, 2-(hydroxymethyl)-1,3-butanediol, 2-(hydroxymethyl)-1,4-butanediol, 2-ethyl-1,2, 3-Propanetriol, trimethylolpropane, 2,4-dihydroxy-3-hydroxymethylpentane, 2-hydroxymethyl-3-methylbutane-1,3-diol, 2-methylpentane-1,3,5-triol, 3-methylpentane-1,3,5-triol, 2-methylpentane-1,2,3-triol, 3-methylpentane-1,2,5-triol, 1,2,3-hexanetriol, hexane-1,2,4-triol, 1,2,5-hexa polyols having three alcoholic hydroxyl groups, such as 1,2,6-hexanetriol, 1,3,5-hexanetriol, 1,4,5-hexanetriol, hexane-1,3,6-triol, hexane-2,3,4-triol, 2,2-di(hydroxymethyl)-3-butanol, 3-hydroxymethyl-1,5-pentanediol, 3,3-dimethyl-1,2,4-butanetriol, and 2-isopropylpropane-1,2,3-triol;and polyols having four alcoholic hydroxyl groups such as 1,2,3,4-butanetetraol, 1,1,4,4-butanetetraol, pentaerythritol, 1,1,5,5-pentanetetraol, 1,2,3,5-pentanetetraol, 1,2,4,5-pentanetetraol, 2-methyl-1,2,3,4-butanetetraol, 1,2,4,5-hexanetetraol, 1,2,5,6-hexanetetraol, 2,2-bis(hydroxymethyl)-1,4-butanediol, and 4-methylpentane-1,2,4,5-tetraol. The polyol of the trifunctional or higher polymerizable compound (B2) is preferably trimethylolpropane.;

[0028] The number of ethylene oxide groups added to the polyol of the trifunctional or higher polymerizable compound (B2) may be 1 or more, and more preferably 2 or more; on the other hand, it is preferably 12 or less, more preferably 9 or less, even more preferably 6 or less, and may be 5 or less. If the number of ethylene oxide groups added to the polyol of the polymerizable compound (B2) is too large, the adhesion of the cured layer may decrease, and further the scratch resistance may decrease.

[0029] The trifunctional polymerizable compound (B2) may be a compound obtained by reacting an ethylene oxide adduct of a polyol with a compound having a polymerizable functional group (e.g., a (meth)acryloyl group); a compound obtained by esterifying an ethylene oxide adduct of a polyol with three (meth)acrylic acids is preferred. The (meth)acrylic acid is either or both of acrylic acid and (meth)acrylic acid.

[0030] The content of the polymerizable compound (B2) in the varnish composition is preferably 10% by mass or more, more preferably 15% by mass or more, based on the entire composition; on the other hand, it is preferably 30% by mass or less, more preferably 25% by mass or less. The content of the polymerizable compound (B2) in the varnish composition is preferably 30% by mass or more, more preferably 40% by mass or more, based on the entire polymerizable monomer (B); on the other hand, it is preferably 70% by mass or less, more preferably 60% by mass or less. When the content of the polymerizable compound (B2) in the varnish composition is at a certain level or more, the curability of the cured layer of the varnish composition is increased, and the surface hardness is also increased. On the other hand, when the content of the polymerizable compound (B2) in the varnish composition is too high, the flexibility and stretchability of the cured layer of the varnish composition are easily deteriorated, and the ruled line cracks are easily generated in the printed matter.

[0031] 1-2-3. Other polymerizable compounds (B3) The polymerizable monomer (B) may contain "another polymerizable compound (B3)" other than the polymerizable compounds (B1) and (B2). The other polymerizable compound (B3) may have one, two or three or more polymerizable functional groups, preferably (meth)acryloyl groups. The other polymerizable compound (B3) is preferably liquid at room temperature (25°C) so that the varnish composition becomes a solution.

[0032] Examples of the polymerizable compound (B3) having one (meth)acryloyl group include alkyl (meth)acrylates such as methyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; aralkyl (meth)acrylates such as benzyl (meth)acrylate; alkoxyalkyl (meth)acrylates such as butoxyethyl (meth)acrylate; (meth)acrylic acid esters of polyalkylene glycol monoalkyl ethers such as diethylene glycol monoethyl ether, triethylene glycol monobutyl ether, and dipropylene glycol monomethyl ether; (meth)acrylic acid esters of polyalkylene glycol monoaryl ethers such as hexaethylene glycol monophenyl ether; and others such as isobornyl (meth)acrylate; glycerol (meth)acrylate; and 2-hydroxyethyl (meth)acrylate.

[0033] Examples of the polymerizable compound (B3) having two (meth)acryloyl groups include bisphenol A di(meth)acrylate, bisphenol F di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, glycerol di(meth)acrylate, neopentyl glycol di(meth)acrylate, and the like.

[0034] Examples of the polymerizable compound (B3) having three or more (meth)acryloyl groups include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, and the like.

[0035] At least a part of the other polymerizable compound (B3) is preferably a polyfunctional polymerizable compound, more preferably a polymerizable compound having two (meth)acryloyl groups. For example, at least a part of the polymerizable compound (B3) is preferably tripropylene glycol di(meth)acrylate or 1,6-hexanediol di(meth)acrylate. By making the other polymerizable compound (B3) polyfunctional, the surface hardness of the cured layer of the varnish composition can be increased (scratch resistance can be increased).

[0036] 1-3. Initiator (C) The initiator (C) contained in the varnish composition may be any substance that generates radicals when irradiated with active energy rays. The initiator (C) is not particularly limited, but may be broadly classified into photocleavage type and hydrogen abstraction type. Specific examples of the initiator (C) include acetophenone, 2,2-diethoxyacetophenone, p-dimethylaminoacetophenone, benzophenone, 2-chlorobenzophenone, p,p'-bisdiethylaminobenzophenone, benzoin ethyl ether, benzoin n-propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, benzoin n-butyl ether, benzoin dimethyl ketal, thioxanthone, p-isopropyl-α-hydroxyisobutylphenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 2,4,6-trimethylbenzophenone, 4-methylbenzophenone, 2,2-dimethoxy-1,2-diphenylethanone, and diphenyl-2,4,6-trimethylbenzoylphosphine oxide. It is preferable to select an initiator (C) that easily absorbs the active energy rays irradiated in the lamicoat process; for example, it is preferable to have a hydroxyalkylphenone structure, such as 1-hydroxycyclohexyl phenyl ketone or 2-hydroxy-2-methyl-1-phenylpropan-1-one. It may also be preferable to select an initiator (C) that is easily soluble in the polymerizable monomer (B).

[0037] The content of the initiator (C) in the varnish composition is preferably 0 to 20% by mass based on the entire varnish composition. Although the varnish composition has active energy ray curability, for example, when it is cured by electron beam, it may be preferable not to include the initiator (C). On the other hand, when the varnish composition is cured by ultraviolet ray, the content of the initiator (C) based on the entire varnish composition is 0.1% by mass or more, preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 8% by mass or more. On the other hand, the content of the initiator (C) based on the entire varnish composition is 20% by mass or less, preferably 15% by mass or less.

[0038] The initiator (C) can impart curability to the varnish composition, and if the content of the initiator (C) in the varnish composition is too low, the curability of the varnish composition is insufficient, and the cured layer of the printed matter tends to have tack or low scratch resistance. In addition, the initiator (C) may function as a plasticizer in the varnish composition and its cured layer. For example, if the content of the initiator (C) in the entire varnish composition is 5% by mass or more, preferably 8% by mass or more, the flexibility and stretchability of the cured layer of the varnish composition are improved, and the cracking of the crease in the printed matter is more easily suppressed.

[0039] 1-4. Silicone compounds (D) The silicone compound (D) contained in the varnish composition may be polysiloxane, modified silicone oil, polysiloxane containing trimethylsiloxysilicate, silicone acrylic resin, etc. The silicone compound (D) can function as a wax in the varnish composition, improving the film peelability from the cured layer of the varnish composition. In addition, the silicone compound (D) preferably also functions as a leveling agent.

[0040] The content of the silicone compound (D) in the varnish composition is 0.1% by mass or more, more preferably 0.2% by mass or more, based on the entire varnish composition; on the other hand, it is 0.5% by mass or less, preferably 0.4% by mass or less. When the content of the silicone compound (D) is a certain amount or more, the film peelability is improved, and the surface slipperiness of the cured layer is improved, improving the scratch resistance.

[0041] 1-5. Optional ingredients The varnish composition may contain, as necessary, ultraviolet absorbers, light stabilizers, antioxidants, antibacterial and antifungal agents, antistatic agents, colorants, lubricants, fillers, latent curing agents, flame retardants, plasticizers, and the like.

[0042] Examples of the ultraviolet absorber include organic ultraviolet absorbers such as salicylic acid-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, triazine-based ultraviolet absorbers, and cyanoacrylate-based ultraviolet absorbers, and inorganic ultraviolet absorbers consisting of fine particles of zinc oxide, titanium oxide, or cerium oxide.

[0043] Examples of light stabilizers include HALS (hindered amine light stabilizers); specifically, bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate, 1-(methyl)-8-(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate, decanedioic acid bis(2,2,6,6-tetramethyl-1-(octyloxy)-4-piperidinyl)ester, bis(1,2,2,6,6-pentamethyl-4-piperidinyl)-[[3,5-bis1,1-dimethylethyl]-4-hydroxyphenyl]methyl-butylmalonate, and dimethyl succinate-1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine polycondensate.

[0044] Examples of the antibacterial and antifungal agents include silver-based inorganic compounds, binazine, preventol, thiebendador, benzimidazole, and thiazolylsulfamide compounds.

[0045] Antistatic agents include positive ion types such as alkylamine sulfate type, quaternary ammonium salt type, and pyridinium salt type, and amphoteric ion types such as alkylbetaine type and alkylimidazoline type. Quaternary ammonium salt type is particularly preferred, and examples thereof include low molecular weight surfactants and acrylate copolymers containing quaternary ammonium bases.

[0046] Furthermore, the varnish composition may contain no solvents (organic solvents and water) or may contain small amounts of solvents (for example, 5% by mass or less, 3% by mass or less, and preferably 1% by mass or less, based on the total amount of the varnish composition).

[0047] 2. Creating printed materials using lamicoat processing The active energy ray-curable varnish composition of the present invention can be used for producing printed matter by lami-coating. The process for producing printed matter by lami-coating comprises at least the following steps A to D. (Step A) The active energy ray-curable varnish composition of the present invention is applied onto the surface of a substrate to form a coating layer. (Step B) A polyolefin film is superimposed and adhered onto the coating layer of the active energy ray-curable varnish composition to form a laminate. (Step C) The laminate is irradiated with active energy rays from the polyolefin film side to cure the coating layer to form a cured layer. (Step D) The polyolefin film is peeled off from the cured layer to obtain a printed matter (laminate).

[0048] The substrate in (Step A) may be a paper substrate, a film substrate, a metal substrate, etc., but is preferably a paper substrate or a film substrate. The paper substrate is not particularly limited, but may be UF coated paper, coated cardboard, art paper, polyethylene coated paper, matte coated paper, etc. The substrate may be plain or have a pattern layer made of printing ink.

[0049] The means for applying the active energy ray curable varnish composition is not particularly limited, and in addition to flexographic printing, known means such as gravure coating, gravure reverse coating, gravure offset coating, spin coating, roll coating, reverse roll coating, kiss coating, dip coating, silk screen coating, wire bar coating, flow coating, comma coating, pouring coating, and spray coating can be applied. A means that does not require solvent dilution is preferable. The amount of the active energy ray curable varnish composition applied to the substrate is preferably such that the thickness of the coating layer is about 3 μm to 10 μm, but may be set according to the application of the printed matter.

[0050] The material of the polyolefin film in (step B) may be a polyolefin such as polyethylene or polypropylene. The polyolefin film can transmit the active energy rays irradiated in (step C). The surface of the polyolefin film (the surface in contact with the coating layer made of the active energy ray curable varnish composition) may have a surface shape such as a flat pattern, a hologram pattern, an embossed pattern, or the like. The surface shape can be transferred to the coating film to impart cosmetic properties to the cured layer. A known laminator or the like can be used to bond the polyolefin film to the coating film for adhesion.

[0051] It is preferable that the surface of the polyolefin film in (Step B) (the surface in contact with the coating layer made of the active energy ray-curable varnish composition) has not been subjected to an easy-adhesion treatment.

[0052] In (Step C), the laminate is irradiated with active energy rays to cure the coating layer made of the active energy ray-curable varnish composition. At this time, the active energy rays are irradiated through the polyolefin film to the coating layer made of the active energy ray-curable varnish composition. However, if the substrate is capable of transmitting active energy rays, the active energy rays may be irradiated through the substrate to the coating layer made of the active energy ray-curable varnish composition. The active energy rays to be irradiated are a general term for ionizing radiation, electromagnetic waves, etc., such as electron beams, ultraviolet rays, or gamma rays, but are preferably ultraviolet rays. When curing with ultraviolet rays, the integrated light dose is 50 mJ / cm. 2 If the integrated amount of light is insufficient, the coating layer may not be cured properly, and a suitable cured layer may not be obtained.

[0053] In (step D), the polyolefin film is peeled off from the cured layer. When the polyolefin film is peeled off, a cured layer to which the surface shape of the polyolefin film is transferred is obtained. The peeled off polyolefin film can be reused by repeatedly using it in the lami-coat process.

[0054] After the polyolefin film is peeled off, the surface of the cured layer may be subjected to a surface treatment such as high gloss treatment to further improve the quality of the resulting print. EXAMPLES

[0055] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to the description of the examples. The amounts of the components in the tables are in parts by weight.

[0056] A. Preparation of active energy ray-curable varnish composition The components used in preparing the active energy ray-curable varnish compositions are shown below. The active energy ray-curable varnish compositions of Examples 1 to 7 and Comparative Examples 1 to 5 were prepared by mixing the components according to the formulations shown in Table 1.

[0057] (Resin varnish) ·VS-1063 Varnish: A varnish made by dissolving VS-1063 in the same mass of HDDA (1,6-hexanediol diacrylate). VS-1063 is a styrene homopolymer (Mw=5,500, manufactured by Seiko PMC Corporation). US-1071 Varnish: A varnish made by dissolving US-1071 in the same mass of HDDA. US-1071 is an acid group-containing polystyrene (Mw=10,000, acid value 75mgKOH / g, manufactured by Seiko PMC Corporation). BS261 Varnish: A varnish made by dissolving BS261 in the same mass of HDDA. BS261 is an acrylic resin (product name "Beamset 261", manufactured by Arakawa Chemical Industries, Ltd.).

[0058] (Polymerizable monomer) 5EO-HDDA: Diacrylate of 5 moles of 1,6-hexanediol EO adduct 3EO-TMPTA: Triacrylate of 3 moles of trimethylolpropane EO adduct 6EO-TMPTA: Triacrylate of 6 moles of EO adduct of trimethylolpropane 9EO-TMPTA: Triacrylate of 9 moles of EO adduct of trimethylolpropane ·TPGDA: Tripropylene glycol diacrylate HDDA: 1,6-Hexanediol diacrylate EOEOEA: 2-(2-ethoxyethoxy)ethyl acrylate

[0059] (Additives) Initiator: 1-hydroxycyclohexyl phenyl ketone (product name "Omnirad 184", manufactured by IGM Resins BV) 1711EF: (Product name "Disparlon 1711EF", polyether modified silicone compound, solid content 50% by mass, manufactured by Kusumoto Chemicals Co., Ltd.)

[0060] B. Creating printed materials using Lamicoat processing As shown in FIG. 1, a printed matter was produced by lamination coating using any one of the active energy ray curable varnish compositions of Examples 1 to 7 and Comparative Examples 1 to 5 shown in Table 1. First, one side of a paper substrate (10) made of UF coated paper (manufactured by Oji Materia Co., Ltd.) and one side of a polypropylene film (P-2161, manufactured by Toyobo Co., Ltd., thickness 30 μm) (11) were fixed (upper left end in the figure). Next, 1.0 gram of active energy ray curable varnish composition (12) was dropped onto the surface of the paper substrate (10). Next, the polypropylene film (11) was sandwiched between a first mare bar (diameter 0.1 mm) (13) and a second mare bar (diameter 0.1 mm) (14), and the first mare bar (13) and the second mare bar (14) were simultaneously bar drawn. Thereby, the first mear bar (13) spreads the active energy ray curable varnish composition (12) on the surface of the paper substrate (10), while the second mear bar (14) presses the polypropylene film (11) against the spread active energy ray curable composition layer to adhere it closely. As a result, a laminate of the paper substrate (10), a coating layer of the active energy ray curable varnish composition (12), and the polypropylene film (11) was obtained. The coating layer of the active energy ray curable varnish composition (12) was about 10 μm thick.

[0061] Thereafter, the laminate was irradiated with ultraviolet light from the polypropylene film (11) side using a conveyor-type ultraviolet light irradiation device equipped with a high-pressure mercury lamp. The moving speed of the irradiation device was 40 m / min, and the irradiation intensity was 120 W / cm. 2 After the ultraviolet ray irradiation, the polypropylene film (11) was peeled off to prepare a printed matter for evaluation.

[0062] C. Evaluation of printed matter The obtained prints were evaluated for curability, peelability, adhesion, scratch resistance, gloss, sliding angle, blocking resistance, and crease cracking.

[0063] (Curability) The curability of the obtained print (immediately after production) was evaluated based on the presence or absence of tack on the surface of the cured layer. The presence or absence of tack was judged by whether or not the surface of the cured layer felt sticky when touched with a finger. ○: No tack ×: With tack

[0064] (Removability) When producing a printed matter, when the polypropylene film was peeled off, it was confirmed whether or not a cured layer made of the active energy ray-curable varnish composition adhered to the peeled off polypropylene film. ○: No adhesion was observed ×: Adhesion confirmed

[0065] (Adhesion) Immediately after production and after leaving the prints at room temperature for 24 hours, the cellophane tape attached to the surface of the cured layer of the prints was peeled off, and the state of the cured layer was visually observed to evaluate adhesion. The evaluation results are shown in the columns "Adhesion immediately after" and "Adhesion after 24 hours" in Table 1. (Evaluation of "△ to ◯" means that there were cases where it was evaluated as ◯ and cases where it was evaluated as △.) ○: No peeling between the paper substrate and the cured layer, or peeling occurred together with the paper substrate △: There was some peeling between the paper substrate and the cured layer. ×: Most of the paper substrate and the cured layer were peeled off.

[0066] (Scratch Resistance) The surface of the cured layer of the printed matter (immediately after production) was scratched with a fingernail, and the scratch resistance was visually evaluated by the presence or absence of scratches. ○: No scratches were observed △: Slight scratches occurred ×: Clear scratches were observed

[0067] (Gloss) The 60° reflection gloss value (unit: GU, gloss unit) of the surface of the cured layer of the obtained print (immediately after production) was measured using a Murakami digital gloss meter (manufactured by Murakami Color Laboratory). The results are shown in Table 1.

[0068] (Sliding angle) For the obtained prints (immediately after production), the sliding angle (unit: °) of the surface of the cured layer was measured using a sliding angle tester manufactured by Toyo Seiki Seisakusho Co., Ltd. under environmental conditions of an atmospheric temperature of 23°C and a humidity of 50%.

[0069] (Blocking resistance) The obtained printed matter (immediately after production) was placed in contact with the cured layers of the printed matter facing each other, and left for 24 hours under a load of 1 kg in an environment of 50°C and 80% RH. After that, the blocking resistance was evaluated by visually checking whether there was any peeling resistance when the contact was released and whether the cured layers had peeled off. ○: No peeling resistance was observed, and peeling of the cured layer was not observed. △: Peel resistance was observed, but peeling of the cured layer was not observed. ×: Peeling of the cured layer was observed.

[0070] (Creasing of Crease Lines (Flexibility)) The resulting print (immediately after curing) was folded 180° and evaluated according to the following evaluation criteria. ○: No creases or fine cracks were observed in the cured layer when the sheet was bent. △: Fine cracks occurred in the cured layer when bent. ×: When bent, cracks occurred in the cured layer.

[0071] [Table 1]

[0072] As shown in Comparative Examples 1 to 3, printed matter obtained using a varnish composition that does not contain 5EO-HDDA, which is a bifunctional polymerizable compound (B1) having an ethylene oxide adduct skeleton of a polyol, has cracked lines and is poor in flexibility. Furthermore, as can be seen from Comparative Example 3, when EOEOEA (2-(2-ethoxyethoxy)ethyl acrylate), which is a monofunctional polymerizable compound, is blended instead of 5EO-HDDA, scratch resistance is also reduced.

[0073] As shown in Comparative Example 4, the printed matter obtained using a varnish composition containing an acrylic resin without a polystyrene resin had poor peelability and reduced scratch resistance. Also, as shown in Comparative Example 5, the printed matter obtained using a varnish composition containing a styrene resin containing an acid group had reduced adhesion and scratch resistance. Thus, it can be seen that by adding a styrene homopolymer (a styrene resin with a high styrene content), scratch resistance is increased and peelability and adhesion are improved.

[0074] In contrast, as shown in Examples 1 to 7, printed matter obtained using a varnish composition containing 5EO-HDDA, a bifunctional polymerizable compound (B1) that contains a styrene homopolymer and has an ethylene oxide adduct skeleton of a polyol, is found to have sufficient peelability, adhesion, scratch resistance, gloss (leveling ability), and flexibility.

[0075] Furthermore, as shown in Examples 3 to 5, when the content of 5EO-HDDA, which is a bifunctional polymerizable compound (B1) having an ethylene oxide adduct skeleton of a polyol, is in the range of approximately 5 to 20 mass % relative to the entire composition, it is found that a printed matter having sufficient peelability, adhesion, scratch resistance, gloss (leveling property), and flexibility is formed.

[0076] In addition, as shown in Examples 3, 6 and 7, it is found that the curability of the cured layer is sufficiently improved by blending 3EO-TMPTA, 6EO-TMPTA and 9EO-TMPTA, which are trifunctional polymerizable compounds (B2) having an ethylene oxide adduct skeleton of a polyol. However, it is found that as the number of ethylene oxide adducts in the polymerizable compound (B2) increases, the adhesion tends to decrease and the scratch resistance also tends to decrease.

[0077] Furthermore, it is found that the adhesion and flexibility can be further improved by adjusting the content of the initiator as shown in Examples 1 to 3. The reason for such improvement in adhesion and flexibility is not limited, but is thought to be because the initiator functions as a plasticizer in the varnish composition or the cured product layer, or because an increase in the polymerization terminal reduces the molecular weight (degree of polymerization) of the cured product, resulting in soft physical properties. [Industrial Applicability]

[0078] The active energy ray curable varnish composition of the present invention is used for producing printed matter by lami-coating (LC processing), and can improve the quality of the printed matter. The quality of the printed matter means that the cured matter layer of the varnish composition has high adhesion, the (surface) hardness of the cured matter layer is high (scratch resistance, etc.), the gloss of the cured matter layer is high (sufficient leveling), the surface of the cured matter layer has high slipperiness, no blocking occurs even when the cured matter layers are in contact with each other, and the cured matter layer has high flexibility and stretchability (suppression of cracking of creases). Therefore, the range of application of the production of printed matter by lami-coating is further expanded, and the market expansion of lami-coating is contributed. [Explanation of symbols]

[0079] 10 Paper base material 11 Polypropylene film 12 Varnish composition 13 First Mare Bar 14 The Second Mare Bar

Claims

1. The active energy ray-curable varnish composition is for a laminate obtained by overlaying a polyolefin film on a coating layer made of an active energy ray-curable varnish composition formed on a substrate, curing the coating layer by irradiation with active energy rays to form a cured material layer, and peeling the polyolefin film from the cured material layer, An active energy ray-curable varnish composition comprising the following (1) to (4): (1) A styrene-based resin (A) of 10.0 to 40.0% by mass relative to the entire composition, the mass ratio of styrene being 95% or more and the acid value being 0 mgKOH / g or 0 to 10 mgKOH / g; (2) a polymerizable monomer (B) containing a bifunctional polymerizable compound (B1) having an ethylene oxide adduct skeleton of a polyol; (3) 0.1 to 20.0% by mass of an initiator (C) based on the total mass of the composition; (4) 0.1 to 0.5 mass % of a silicone-based compound (D) based on the total mass of the composition.

2. The active energy ray-curable varnish composition according to claim 1 , wherein the styrene-based resin (A) is a styrene homopolymer.

3. 3. The active energy ray-curable varnish composition according to claim 1, wherein the styrene-based resin (A) has a mass average molecular weight of 3,000 to 8,000.

4. 3. The active energy ray-curable varnish composition according to claim 1, wherein the polyol of the bifunctional polymerizable compound (B1) having an ethylene oxide adduct skeleton of a polyol is a polyol having 4 to 8 carbon atoms.

5. 3. The active energy ray-curable varnish composition according to claim 1, wherein the bifunctional polymerizable compound (B1) having an ethylene oxide adduct skeleton of a polyol has an ethylene oxide addition number of 3 to 8.

6. The active energy ray-curable varnish composition according to claim 1 or 2, wherein the bifunctional polymerizable compound (B1) having an ethylene oxide adduct skeleton of a polyol is a diacrylate of a 5-mol ethylene oxide adduct of 1,6-hexanediol (5EO-HDDA).

7. 3. The active energy ray-curable varnish composition according to claim 1, wherein the content of the bifunctional polymerizable compound (B1) having an ethylene oxide adduct skeleton of a polyol is 20.0 mass% or less based on the total mass of the composition.

8. The active energy ray-curable varnish composition according to claim 1 or 2, wherein the initiator (C) has a hydroxyalkylphenone structure.

9. 3. The active energy ray-curable varnish composition according to claim 1, wherein the content of the initiator (C) is 8.0 mass% or more based on the total mass of the composition.

10. 3. The active energy ray-curable varnish composition according to claim 1, wherein the polymerizable monomer (B) further comprises a tri- or higher functional polymerizable compound (B2) having an ethylene oxide adduct skeleton of a polyol.

11. The active energy ray-curable varnish composition according to claim 10, wherein the polyol of the tri- or higher functional polymerizable compound (B2) having an ethylene oxide adduct skeleton of a polyol is trimethylolpropane.

12. The active energy ray-curable varnish composition according to claim 10, wherein the tri- or higher functional polymerizable compound (B2) having an ethylene oxide adduct skeleton of a polyol has an ethylene oxide addition number of 1 to 12.

13. The active energy ray-curable varnish composition according to claim 10, wherein the content of the tri- or higher functional polymerizable compound (B2) having an ethylene oxide adduct skeleton of a polyol is 10.0 to 30.0 mass% based on the total mass of the composition.

Citation Information

Patent Citations

  • Precipitate scraper

    JP1981017610A

  • X-ray high voltage device

    JP1984078497A

  • Method for processing surface of printed matter

    JP2007090162A

  • Active energy ray-curable varnish composition

    JP2012136618A

  • Active energy ray-curable varnish composition

    JP2021080354A